T and genetic variations between Asian and Caucasian polypoidal choroidal vasculopathy. Issue 12 (9th October 2020) - Jordan-Yu, Janice Marie; Teo, Kelvin; Fan, Qiao; Gana, Jose Carlos; Leopando, Anna Karina; Nunes, Sandrina; Farinha, Cláudia; Barreto, Patricia; Melo, Joana Barbosa; Carreira, Isabel; Murta, Joaquim Neto; Silva, Rufino; et al.
Abstract : Purpose: To compare phenotypic and genetic variations in polypoidal choroidal vasculopathy (PCV) between Caucasian and Asian patients. Methods: We analysed phenotypic and genotypic data from two sites, Association for Innovation and Biomedical Research on Light and Image, Portugal and Singapore National Eye Centre, Singapore. Baseline fundus photography, spectral domain-optical coherence tomography, indocyanine green and fluorescein angiography scans were analysed by respective reading centres using a standardised grading protocol. Single nucleotide polymorphisms across 8 PCV loci were compared between cases and controls selected from each population. Results: One hundred and forty treatment-naïve PCV participants (35 Portuguese and 105 Singaporean) were included. The Portuguese cohort were older (72.33±8.44 vs 68.71±9.40 years, p=0.043) and were comprised of a lower proportion of males (43% vs 71%, p=0.005) compared with the Singaporean cohort. Differences in imaging features include higher prevalence of soft drusen (66% vs 30%, p=0.004), lower prevalence of subretinal haemorrhage (14% vs 67%, p<0.001), smaller polypoidal lesion (PL) area (0.09±0.09 vs 0.76±0.93 mm 2, p<0.001), lower ratio of PL to branching vascular network area (3% vs 38%, p<0.001) and lower central retinal thickness (346.48±93.74 vs 493.16±212.92 µm, p<0.001) in the Portuguese cohort. CETP rs3764261 (OR 2.467; 95% CI 1.282 to 4.745, p=0.006) in the Portuguese population was significantly associated with PCV and CFH rs800292 (OR 1.719; 95% CI 1.139 to 2.596, p=0.010) in the Singaporean population, respectively. Conclusion: Among Asian and Caucasian patients with PCV, there are significant differences in the expression of phenotype. We also identified different polymorphisms associated with PCV in the two populations.